Childhood ADHD and subthreshold symptoms are associated with cognitive functioning at age 40—a cohort study on perinatal birth risks - Schiavone, Nella; Virta, Maarit; Leppämäki, Sami; Launes, Jyrki; Vanninen, Ritva; Tuulio-Henriksson, Annamari; Järvinen, Ilkka; Lehto, Eliisa; Hokkanen, Laura (Frontiers in Psychology, 2024)
In this prospective cohort study over 40 years we investigated the effect of childhood attentiondeficit/hyperactivity disorder (ADHD) and subthreshold ADHD on cognitive performance in adulthood. The cohort comprised individuals with mild perinatal risks. Childhood ADHD group (cADHD, n = 39) was compared to a group with subthreshold childhood attention or hyperactivity symptoms (cAP; n = 79), a group with similar perinatal risks but no ADHD symptoms (n = 255), and to controls without ADHD symptoms or perinatal risks (n = 69). The groups were assessed with multiple neuropsychological measures in domains of verbal reasoning, perceptual skills, memory, working memory, attention, executive functions, and speed. Group-level differences and frequencies of deficient functioning were analyzed. Overall, the groups' performance differed in all cognitive domains at age 40. Verbal reasoning, perceptual skills, memory, and speed had the largest effect sizes (.51 -.62). The cADHD group's performance was lower than the other groups' on 13 out of 21 measures. The cAP group performed poorer than controls on five measures. In the cADHD group, 23% had three or more deficient cognitive domains, compared to 4%-6% in the other groups. Childhood ADHD is associated with impaired cognitive functioning in adulthood on several cognitive domains whereas childhood subthreshold ADHD is linked to fewer cognitive deficits. Task complexity was linked to poorer performance within the ADHD group. Our results add to the scarce longitudinal evidence of cognitive outcomes related to childhood ADHD and subthreshold symptoms.